Edaphic Entomofauna Variation Depending on Glyphosate Application in Roundup Ready Soybean Crops - PEREIRA,J.L. (2018)
ABSTRACT: Currently, biomonitoring is a methodology used to verify the environmental impact of new technologies in the agricultural environment, highlighting edaphic entomofauna that is traditionally used as a bioindicator in this sort of research. Therefore, the objective of this study was to investigate the edaphic entomofauna variation depending on glyphosate application in Roundup Ready soybeans. The experiment was carried out in Coimbra, MG during the 2007/2008 and 2008/2009 cropping seasons. The experimental design was a randomized block design with five replications. The treatments were: non-transgenic soybean with mechanical weeding of weeds; transgenic soybean with mechanical weeding of weeds; transgenic soybean with one glyphosate application and transgenic soybean with three glyphosate applications. The populations of the edaphic entomofauna were sampled during two crops. The insertion of the glyphosate tolerance gene did not affect the richness and the abundance of arthropods in the soil. The arthropod richness was reduced in treatments where glyphosate was applied one and three times. The glyphosate application in transgenic soybean reduced the density of the predatory mite Galumnidae (Acari); predator ants Neivamyrmex sp. (Hymenoptera: Formicidae) and Solenopsis sp. (Hymenoptera: Formicidae); and springtails Entomobryidae (Collembola), Hypogastrura sp. (Collembola: Hypogastruridae) and Onychiuridae (Collembola). Therefore, it is essential to follow the use recommendations of the herbicide glyphosate and adopt good agricultural practices that promote pesticide biodegradation, thereby contributing to the reduction of the toxicological potential of glyphosate on the edaphic entomofauna.